Changes in blood lipids in patients with chronic hepatitis B after 48 weeks of tenofovir alafenamide treatment: A prospective real-world clinical study. Issue 2 (3rd April 2022) - Zhang, Yeqiong; Li, Zhipeng; Luo, Qiumin; Xu, Wenxiong; Wang, Lu; Zhu, Shu; Peng, Liang; Xie, Chan
Background: Tenofovir alafenamide (TAF) is a new anti-hepatitis B virus nucleotide analogue that can cause dyslipidaemia in AIDS patients, but the effect of TAF on blood lipids in patients with chronic hepatitis B (CHB) is unknown. This study aimed to evaluate the effect of TAF on blood lipid levels in patients with CHB. Methods: One hundred and twenty-one CHB patients were recruited as TAF group, including 69 treatment-naïve patients and 52 patients with nucleoside/nucleotide analogue experience before TAF treatment. All patients were followed up regularly for 48 weeks. Total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and triglyceride (TG) levels and the incidence of dyslipidaemia before and after TAF treatment were compared. Results: After 48 weeks of TAF treatment, the levels of TC, TGs and LDL-C in TAF group were significantly higher than those in control group. In TAF group, the TC and TG levels were significantly higher than that at baseline. Baseline TC and TGs levels had a significant effect on the incidence of abnormal TC and TG levels after 48 weeks treatment. The LDL-C decreased slightly but not significantly. The proportion of patients with TC abnormalities increased from 20.7% at baseline to 26.3% at week 48, LDL-C abnormalities decreased from 50.4% to 42.5% and TG abnormalities increased from 14.2% to 22.5%. There were no significant differences compared with control group, as well as compared with baseline. Conclusions: Tenofovir alafenamide treatment mainly affects the TC and TG level in patients with CHB but has little effect on LDL-C.